A modified strength degradation model of 45 steel under cyclic loading. Issue 1 (1st January 2022) - Qu, Yang; Liu, Xintian; Zhang, Minghui; Liang, Zhiqiang
ABSTRACT: In this paper, a modified degradation model is proposed to simulate the residual strength of 45 steel under cyclic loading, which is then applied to analyse the rule of strength degradation of the metal. The degradation data of 45 steel tests shows the relationship between the ratio of cycle number and residual strength. The model is built by considering a series of cycle ratio errors between loading times and fatigue life on the basis of the Schaff theory and power degradation model criterion. The model is applied to numerical simulation of 35CrMo, with the outcome being presented to illustrate the applicability and efficiency of the model. Moreover, the results provide some theoretical references for the fatigue life analysis of metals.